Hollow nanotube arrays of nickle–cobalt metal sulfide for high energy density supercapacitors. Issue 8 (14th February 2023) - Shen, Ding; Li, MingYue; Liu, Yaohan; Fu, Xiaofan; Yu, Haoran; Dong, Wei; Yang, ShaoBin
Abstract : Electrochemical performance of the NiCo2 S4 hollow nanotube array as a promising electrode material for high energy density supercapacitors. Abstract : High energy density is still difficult to achieve using existing metal sulfides because of their low specific capacitance. To improve capacitance, a series of nickel and cobalt metal sulfides with different Ni/Co ratios were synthesized by a two-step hydrothermal method. Using the combining method of experimental research and first-principles calculation, the morphology, structural stability, electronic structure and electrochemical properties of metal sulfides were investigated systematically. The results show that the morphology of metal sulfides gradually grows from two-dimensional structure to nanotube arrays, and finally to nanorod arrays, as the Ni/Co ratios decrease. Among them, the NC24 sample with the Ni/Co ratio of 1 : 2 is a hollow nanotube array composed of NiCo2 S4, which shows excellent electrochemical performance. The specific capacity of the NC24 sample reaches 1527C g −1 at 1 A g −1, and the capacity retention is 93.81% at 10 A g −1 after 2000 cycles. Furthermore, a symmetrical supercapacitor assembled from the NiCo2 S4 nanotube array shows a high energy density of 67.5 W h kg −1 . This strategy develops a nanotube array of metal sulfides and expands its application in a high energy density supercapacitor.